The role of endovideolaparoscopic technologies in the diagnosis and treatment of acute abdominal diseases in young infants (Texas Journal of Medical Science, 2022)
The article demonstrates the results of emergency treatment of abdominal diseases in 174 young children. Diagnostic criteria and also therapeutic tactics of various acute surgical diseases occurring in the abdominal cavity are given. Surgical intervention was performed on 97 patients. Most operations are performed by video laparoscopic method. There were no complications during and after surgery